Infection frequency of hepatitis C virus and IL28B haplotypes in Papua New Guinea, Fiji, and Kiribati. - G L Abby Harrison; Jan Pryor; Joji Malani; Mathias Supuri; Andrew Masta; Burentau Teriboriki; Tebuka Toatu; David Penny; Jean-Pierre Allain; Eleanor Barnes; Oliver G Pybus; Paul Klenerman (PLoS ONE)
It has been estimated that there are more than 60 million Hepatitis C virus (HCV) carriers in the World Health Organisation's Western Pacific region (WHO-WPR), where liver cancer is among the top three causes of cancer death. WHO and the US Centres for Disease Control and Prevention report the prevalence of HCV in the South Pacific islands (countries within the WHO-WPR) to be high (5-10% and >2% respectively). However, since HCV is not tested for in many of these countries, there is sparse data available to support this assertion. We screened ∼2000 apparently healthy individuals from Papua New Guinea, Fiji and Kiribati and found a sero-prevalence of 2.0%, 0.1% and 0%, respectively. All sero-positive samples tested negative for HCV RNA. Curious as to why all the sero-positive individuals were negative for HCV-RNA, we also screened them for the HCV protective IL28B SNP markers rs12979860 and rs8099917. All antibody-positive participants bar one had HCV protective haplotypes. Our results suggest that HCV is present in these Pacific island countries, albeit at a prevalence lower than previous estimates. As none of our participants had undergone antiviral treatment, and therefore must have cleared infection naturally, we hypothesise that genotypes 1 and/or 4 are circulating in South Pacific Island people and that these peoples are genetically predisposed to be more likely to spontaneous resolve HCV infection than to become chronic carriers.